Electrical-Field-Driven Tunable Spectral Responses in a Broadband-Absorbing Perovskite Photodiode. - Tang, Xiaofeng; Matt, Gebhard; Gao, Shuai; Gu, Ening; Almora, Osbel; Brabec, Christoph (ACS Applied Materials and Interfaces, 2019)
Controllably manipulating the spectral response of broadband-absorbing semiconductors is crucial for developing wavelength-selective optoelectronic devices. In this article, we report for the first time, the bias-dependent spectral responses for a metal-halide perovskite photodiode. Tunable external quantum efficiencies in the short- and long-wavelength regimes, and the full spectral range (ca. 300-800 nm) are observed when the device is operated under short-circuit, and forward and reverse bias conditions, respectively. This observation is understood by the interplay of wavelength-dependent penetration depth and barrier formation within the photodiode device stack. The general applicability of this concept is confirmed by a systematic study on a series of mixed-halide perovskite devices. These results suggest that the proposed concept allows as a promising platform and should inspire further exploration of multispectral responsive optoelectronic devices.
Keywords: perovskite; optoelectronics; electrodeposition; mixed-halide perovskite; external quantum efficiency

Exploring the Stability of Novel Wide Bandgap Perovskites by a Robot Based High Throughput Approach - Chen, Shi; Hou, Yi; Chen, Haiwei; Tang, Xiaofeng; Langner, Stefan; Li, Ning; Stubhan, Tobias; Levchuk, Ievgen; Gu, Ening; Osvet, Andres; Brabec, Christoph (Advanced Energy Materials, 2017)
Currently, lead-based perovskites with mixed multiple cations and hybrid halides are attracting intense research interests due to their promising stability and high efficiency. A tremendous amount of 3D and 2D perovskite compositions and configurations are causing a strong demand for high throughput synthesis and characterization. Furthermore, wide bandgap (≈1.75 eV) perovskites as promising top-cell materials for perovskite–silicon tandem configurations require the screening of different compositions to overcome photoinduced halide segregation and still yielding a high opencircuit voltage (Voc). Herein, a home-made high throughput robot setup is introduced performing automatic perovskite synthesis and characterization. Subsequently, four kinds of compositions (i.e., cation mixtures of Cs–methylammonium (MA), Cs– formamidinium (FA), MA–FA, and FA–MA) with an optical bandgap of ≈1.75 eV are identified as promising device candidates. For Cs–MA and Cs–FA films it is found that the Br–I phase segregation indeed can be overcome. Moreover, Cs–MA, MA–FA, and Cs–FA based devices exhibit an average Voc of 1.17, 1.17, 1.12 V, and their maximum values approached 1.18, 1.19, 1.14 V, respectively, which are among the highest Voc (≈1.2 V) values for ≈40% Br perovskite. These findings highlight that the high throughput approach can effectively and efficiently accelerate the invention of novel perovskites for advanced applications.

Local Observation of Phase Segregation in Mixed-Halide Perovskite. - Tang, Xiaofeng; van den Berg, Marius; Gu, Ening; Horneber, Anke; Matt, Gebhard; Osvet, Andres; Meixner, Alfred J.; Zhang, Dai; Brabec, Christoph (Nano Letters, 2018)
Mixed-halide perovskites have emerged as promising materials for optoelectronics due to their tunable bandgap in the entire visible region. A challenge remains however in the photo-induced phase-segregation, narrowing the bandgap of mixedhalide perovskites under illumination thus restricting applications. Here we use a combination of spatially-resolved and bulk measurements to give an in-depth insight into this important yet unclear phenomenon. We demonstrate that photo-induced phase-segregation in mixed-halide perovskites selectively occurs at the grain boundaries rather than within the grain centers by using shear-force scanning probe microscopy in combination with confocal optical spectroscopy. Such difference is further evidenced by light-biased bulk Fourier-transform photocurrent spectroscopy, which shows the iodine-rich domain as a minority phase coexisting with the homogenously mixed phase during illumination. By mapping the surface potential of mixed-halide perovskites, we evidence the higher concentration of positive space charge near grain boundary possibly provides the initial driving force for phasesegregation, while entropic mixing dominates the reverse process. Our work offers detailed insight into the microscopic processes occurring at the boundary of crystalline perovskite grains and will support the development of better passivation strategies, ultimately allowing to process environmentally more stable perovskite films.
Keywords: Perovskite; Photovoltaic; Photoluminescence; Phase-segregation; Scanning probe microscopy; Optical spectroscopy

Robot-Based High-Throughput Screening of Antisolvents for Lead Halide Perovskites - Gu, Ening; Tang, Xiaofeng; Langner, Stefan; Duchstein, Patrick; Zhao, Yicheng; Levchuk, Ievgen; Kalancha, Violetta; Stubhan, Tobias; Hauch, Jens; Egelhaaf, Hans-Joachim; Zahn, Dirk; Osvet, Andres; et al. (Joule, 2020)
Solution-based processing of photovoltaic materials has important advantages, including lower overall costs and easier upscaling of fabrication, where the solvents play an essential role. Antisolvent crystallization technique is often applied to achieve high-quality perovskite materials. However, the basic chemistry of the solvent-antisolvent crystallization is still not well understood. Besides, common antisolvents are toxic, and their number is limited. In this work, a novel robot-based method was used to screen the efficient antisolvents for different solvent-perovskite systems. 336 combinations of perovskite-solvent-antisolvent could be prepared and characterized by the integrated robotic platform in 2 days. In addition, we provided a detailed working mechanism of the solvent-antisolvent crystallization approach. Furthermore, hundreds of potential antisolvents were proposed based on high-throughput screening and simulation. Verification tests match well with theory, and all reported antisolvents used for photovoltaic device optimizations are within our predicted range of the Hansen space, indicating that the predictions are reliable. In terms of solution-processed lead halide perovskite optoelectrical materials, suitable antisolvent is essential for the crystallization and properties of final products. Conventional experiments of antisolvent selections are based on the manual time-consuming trial-error methods, which cannot meet today's increasing demands. In this work, a robot-based method was used to screen the antisolvents for different solvent-perovskite systems in a high-throughput manner to study the influence of interactions among the solvent molecules, cations, metal-halides, and antisolvents, to build an informative database, and to reveal the working mechanism and selection criteria of antisolvents. Besides, simulations based on the screening results provide hundreds of potential antisolvents. Corresponding verification tests evidenced that our predictions are reliable and vital for designing future efficient mixed solvent systems for the fabrication of perovskite optoelectrical materials. A robotic platform is adopted to conduct a comprehensive solvent engineering for making lead halide perovskites in a high-throughput manner. Deeper insights into the working mechanisms and selection criteria of antisolvents are investigated and summarized. In addition, a reliable antisolvent database is established, and verification tests match well with the theory. Furthermore, our work provides significant guidance for designing functional and environment-friendly mixed solvent systems to fabricate high-quality perovskite materials or devices.
CRIS-Team Scopus Importer:2020-08-21
Keywords: antisolvents; automated research; high-throughput method; lead halide complexes; lead halide perovskite; solvent engineering

Single molecular precursor ink for AgBiS2 thin films: synthesis and characterization - Gu, Ening; Lin, Xianzhong; Tang, Xiaofeng; Matt, Gebhard; Osvet, Andres; Hou, Yi; Jäger, Sebastian; Xie, Chen; Karl, André; Hock, Rainer; Brabec, Christoph (Journal of Materials Chemistry C, 2018)
Recently, AgBiS2 has been demonstrated to be a promising non-toxic, earth-abundant absorber material for solar energy application. In this work, a novel route to deposit AgBiS2 thin films from single molecular precursor ink is presented. It is found that the amount of thiourea has a crucial impact on the formulation of a stable molecular ink. Understanding the coordination chemistry of the molecular precursor ink is important for getting better control over the thin film processing. With the assistance of Raman spectroscopy, possible complexation mechanisms and general coordination states within the molecular ink are studied. In addition, the influence of ink composition as well as the annealing temperature on the structure and morphology of resulting AgBiS2 films is systematically investigated. It is found that the crystallinity and particle size increase with higher annealing temperature. The obtained AgBiS2 thin films show a cubic structure with a preferred orientation in [111] direction. Optical and electrical measurements demonstrate that the obtained AgBiS2 is an indirect band gap material, which features two transition mechanisms with an indirect band gap of around 0.87 eV and a direct one of around 1.21 eV. The high absorption coefficient, low Urbach energy and fast transient photoconductivity confirm its potential as an absorber for photovoltaic applications.

Spontaneously Self-Assembly of a 2D/3D Heterostructure Enhances the Efficiency and Stability in Printed Perovskite Solar Cells - Hu, Jinlong; Wang, Chuan; Qiu, Shudi; Zhao, Yicheng; Gu, Ening; Zeng, Linxiang; Yang, Yuzhao; Li, Chaohui; Liu, Xianhu; Forberich, Karen; Brabec, Christoph; Nazeeruddin, Mohammad Khaja; et al. (Advanced Energy Materials, 2020)
As perovskite solar cells (PSCs) are highly efficient, demonstration of high-performance printed devices becomes important. 2D/3D heterostructures have recently emerged as an attractive way to relieving the film inhomogeneity and instability in perovskite devices. In this work, a 2D/3D ensemble with 2D perovskites self-assembled atop 3D methylammonium lead triiodide (MAPbI3) via a one-step printing process is shown. A clean and flat interface is observed in the 2D/3D bilayer heterostructure for the first time. The 2D perovskite capping layer significantly suppresses nonradiative charge recombination, resulting in a marked increase in open-circuit voltage (VOC) of the devices by up to 100 mV. An ultrahigh VOC of 1.20 V is achieved for MAPbI3 PSCs, corresponding to 91% of the Shockley–Queisser limit. Moreover, notable enhancement in light, thermal, and moisture stability is obtained as a result of the protective barrier of the 2D perovskites. These results suggest a viable approach for scalable fabrication of highly efficient perovskite solar cells with enhanced environmental stability.
CRIS-Team Scopus Importer:2020-03-27
Keywords: 2D/3D heterojunctions; high efficiency; perovskite solar cells; self-assembly; stability

Surprising Efficiency Enhancement of Cu2ZnSn(S,Se)4 Solar Cells with Abnormal Zn/Sn Ratios - Ge, Sijie; Xu, Han; Huang, Yuxiang; Karunakaran, Santhosh Kumar; Hong, Ruijiang; Li, Jianjun; Mai, Yaohua; Gu, Ening; Lin, Xianzhong; Yang, Guowei (Solar RRL, 2020)
The elemental proportion of Cu poor and Zn rich in Cu2ZnSn(S,Se)4 (CZTSSe) is well established for achieving highly efficient CZTSSe solar cells. However, how high Zn/Sn ratio can the complicated CZTSSe thin film tolerate remains a question. Therefore, herein, the well control of Zn/Sn ratio in CZTSSe thin film is obtained by multi-spin-coating and tuning the initial Zn/Sn ratio in the Cu–Zn–Sn–S precursor ink from 1.0 to 1.9. It is found that the Zn/Sn on the surface of CZTSSe absorber can self-regulate to around 1.2 even with Zn/Sn ratio up to 1.9 in the precursor solution. Excess Zn presented as Zn(S,Se) secondary phase not only concentrate near the bottom area, but also widely distribute at the grain boundaries (GBs). In addition, it is found that the Zn(S,Se) secondary phase at GBs can promote current transport as revealed by conductive atomic force microscopy measurement. The surface roughness and grain size of the resulting CZTSSe absorber increased, whereas the MoSe2 thickness was reduced with increasing Zn/Sn ratio. More importantly, the device performance increased from 4.5% to 10.0% with a significant decrease in VOC deficit from 0.73 to 0.58 V when the Zn/Sn ratio increases from 1.0 to 1.5 in the precursor ink.
CRIS-Team Scopus Importer:2020-09-25
Keywords: CZTSSe solar cells; low V; self-regulation of surface compositions; Zn/Sn ratios

Utilizing the unique charge extraction properties of antimony tin oxide nanoparticles for efficient and stable organic photovoltaics - Liu, Chao; Félix, Roberto; Forberich, Karen; Du, Xiaoyan; Heumüller, Thomas; Matt, Gebhard; Gu, Ening; Wortmann, Jonas; Zhao, Yicheng; Cao, Yuanyuan; He, Yakun; Ying, Lei; et al. (Nano Energy, 2021)
Simultaneously enhancing device performance and longevity, as well as balancing the requirements on cost, scalability, and simplification of processing, is the goal of interface engineering of organic solar cells (OSCs). In our work, we strategically introduce antimony (Sb3+) cations into an efficient and generic n-type SnO2 nanoparticles (NPs) host during the scalable flame spray pyrolysis synthesis. Accordingly, a significant switch of conduction property from an n-type character to a p-type character is observed, with a corresponding shift in the work function (WF) from 4.01 ± 0.02 eV for pristine SnO2 NPs to 5.28 ± 0.02 eV for SnO2 NPs with 20 mol. % Sb content (ATO). Both pristine SnO2 and ATO NPs with fine-tuned optoelectronic properties exhibit remarkable charge carrier extraction properties, excellent UV resistance and photo-stability being compatible with various state-of-the-art OSCs systems. The reliable and scalable pristine SnO2 and ATO NPs processed by doctor-blading in air demand no complex post-treatment. Our work offers a simple but unique approach to accelerate the development of advanced interfacial materials, which could circumvent the major existing interfacial problems in solution-processed OSCs.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Antimony doped tin oxide; Doping mechanism; Interface engineering; Metal oxide nanoparticles; Organic photovoltaics

Visualizing and Suppressing Nonradiative Losses in High Open-Circuit Voltage n-i-p-Type CsPbI3 Perovskite Solar Cells - Meng, Wei; Hou, Yi; Karl, André; Gu, Ening; Tang, Xiaofeng; Osvet, Andres; Zhang, Kaicheng; Zhao, Yicheng; Du, Xiaoyan; García Cerrillo, José; Li, Ning; Brabec, Christoph (ACS Energy Letters, 2020)
Cesium lead iodide (CsPbI3) has attracted increasing attention for its photovoltaic applications, owing to its thermal stability and suitable band gap for tandem solar cells. However, the severe nonradiative recombination losses in CsPbI3-based perovskite solar cells generally restrict their open-circuit voltage (VOC) to the range of 0.9 to 1.1 V. This work uniquely reports a method to visualize all defect-assisted recombination pathways with photoluminescence (PL) techniques. Visible and valuable insight into the reduction of defect densities on a micrometer scale was obtained by the bottom surface and bulk passivation with barium hydroxide and trioctylphosphine oxide. The dual effects successfully improve the VOC of the solar cell from 0.87 to 1.17 V. These results highlight the potential of hyperspectral PL imaging as a powerful tool to give guidance to further suppress the nonradiative VOC losses in all-inorganic perovskites.
CRIS-Team Scopus Importer:2020-01-21